Dialogue, participation and social innovation initiatives for improving territorial governance in rural environments (Ciudades, 2021)
Territorial governance is a complex concept that mixes reality with purpose. While its theoretical framework includes advanced forms of citizen participation and shared decisions, actual landscape trends show an image of territorial polarization, abandonment and land use change towards urban-centred models. This scenario pushes local population and institutions away from an increasingly centralised and top-down decision-making. Dealing with this situation, this paper analyses three case-studies led by Fundación Entretantos, all of them related to territory-based agricultural production. The analysis summarises the key learnings, constrains and methodological advances that can contribute to a better design and implementation of participatory initiatives aiming to improve territorial governance in rural areas.
Keywords: territorial governance; participation; agroecology; global change